Plasma hardening wear resistant cast iron - Чейлях, А.П.; Куцомеля, Ю.Ю.; Чейлях, Я.А.; Микула, Я. (Problems of Tribology, 2016)
The aim of the research is the study of the regularities of structure formation and the formation of metastable aus-tenite condition for increase of wear resistance of white cast iron. Plasma hardening in solid state at temperatures heat up 800 ... 900° c significantly refines the microstructure of cast iron ChG5D2F4 with high content of residual metastable austenite. Plasma processing with melting surface (t = 1300…1400 °C) provides the differentiation of the microstructure of cast iron on the plane of the impact zone with high content of metastable austenite. X-ray microanalysis allowed us to confirm the pres-ence of spheroidal carbides of vanadium VxC, austenitic-carbide eutectic, low content of Silicon in vanadium carbides and cementite locations in comparison with solid solutions. Plasma hardening of cast iron on the optimal regime without melting the surface (t = 800 ... 900 °C) enhances its abrasive wear resistance in 1.3 times in comparison with the quenching with fur-nace heating, which corresponds to the austenite-martensite-carbide structure with metastable γ - phase. This is grinding of the structure and metastable austenite realizing deformation induced martensitic γ → α’ transformation and self-strengthening effect in a thin surface layer. Keywords: The wear-resistant cast iron, plasma hardening, martensite, metastable austenite, carbide, abrasive wear-resistance.